Taste-related activity in the human dorsolateral prefrontal cortex. - Kringelbach, M; de Araujo, I; Rolls, E (2004)
Taste remains one of the least-explored human senses. Cortical taste responses were investigated using neuroimaging in 40 subjects tasting a range of different taste stimuli compared to a neutral tasteless control. Activation was found in the anterior insula/frontal opercular taste cortex and caudal orbitofrontal cortex, both areas established as taste cortical areas by neuronal recordings in primates. A novel finding in this study was a highly significant response to taste in the dorsolateral prefrontal cortex. This may reflect an effect of taste on cognitive processing to help optimise or modify behavioural strategies involved in executive control; or it could reflect the engagement of this region in attentional processing by a taste input.